PENERAPAN TEKNOLOGI WEB UNTUK MEMBANGUN SISTEM LATIHAN UJIAN NASIONAL ONLINE BAGI SMA MUHAMMADIYAH 4 KARTASURA - Heru Supriyono, Anam Sutopo, Rahma Fitri Wahadati, Kunti Dwi Narwattu Jati, Unsta Nastiti Lingga Ras (Jurnal Ilmiah SINUS, 2017)
In 2015, Ministry of Education and Culture of Republic of Indonesia introduced online national examination systems for senior high school students to replace paper-based national examination systems. The problem faced by many schools are students are not ready to have a computer-based test because they do not have enough preparation. The root this problem is because scholls do not have an online examination systems for training their students. This paper discusses a development and application of online national examination preparation systems for SMA Muhammadiyah 4 Kartasura. The objective of the development is to provide a web based sistem which could be used for training students to face online national examination. The system was developed following system development life cycle (SDLC) principle with waterfall approach. The requirement analysis showed that the features of the systems needed by the school are involving randomizing mechanism for questions, test duration limitation, automatic marking systems, administrator functions and login systems for students and teachers. The national examination preparation systems was developed using PHP programming language dan MySQL database management systems. The result of the development is a web-based national examination preparation systems with complete features in accordance with requirement analysis. The questionaire analysis of system testing by the users involving teachers and students showed that 70% respondents feel satisfy with the developed systems.  Keywords: computer based test, online national examination, web-based test systems,